Chemical element Arsenic - Semenov I. V., Iakovleva I. V. (Fall School Marathon, 2019)
The article describes the chemical element As, presents its physical properties and a number of areas of application.
Keywords: мышьяк; arsenic; химический элемент As; физические свойства мышьяка